Kinematics of path tracking at singularities of the planar 2R manipulator - Kieffer, Jon (Zielona Góra: Uniwersytet Zielonogórski)
A method for determining the differential kinematics of path tracking at singular configurations of the planar 2R manipulator is presented. The method is based on Taylor series analysis of the displacement equations to determine low-order parametric curves that satisfy those equations.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka